Pengaruh Digital Marketing Dan Kualitas Produk Terhadap Kepuasan Konsumen Pada Brand Clothing Locke Peke Di Kota Bima - ISMUNANDAR IS; INTISARI HARYANTI (Journal of Innovative and Creativity, 2025)
This study aims to identify and analyze the influence of Digital Marketing and Product Quality on Consumer Satisfaction in the “Locke Peke” clothing brand in Bima City. Digital marketing is a promotional strategy that utilizes digital technology to reach a wider audience, while product quality includes durability, design, comfort, and how well the product meets consumer expectations. The research method used is a quantitative approach with multiple linear regression to examine the relationship between variables. Data were collected through questionnaires distributed to 96 respondents who are consumers of the Locke Peke brand. The research findings indicate that Digital Marketing has a significant influence on consumer satisfaction, meaning that a well-executed digital marketing strategy can enhance consumers’ positive perceptions of the brand. However, the Product Quality variable does not show a significant influence on consumer satisfaction, possibly due to consumer perception that the product quality is already adequate or that other factors such as price or fashion trends are more influential. The R-Square value of 0.364 indicates that 36.4% of the variation in consumer satisfaction can be explained by the Digital Marketing and Product Quality variables, while the remaining 63.6% is influenced by other factors not examined in this study. This research is expected to provide useful insights for local clothing businesses to focus more on developing effective digital marketing strategies to increase customer satisfaction.